The Development of Information Systems for Measuring Student Performance at MTs Al-Azhar Paseseh Tanjung Bumi - Achmad Jauhari; Fifin Ayu Mufaroha (International Journal of Science, Engineering, and Information Technology, 2019)
Education becomes a compulsive program set by the government by implementing a 12-year compulsory education to improve human resources in Indonesia. A part of primary education concerns and results from measurement of student performance, that we call it school report cards. The main aim of this research is to build a school grade information system to help teacher and the homeroom teacher in input school report cards. Development of this system has built by applying the waterfall model. Data obtain to making this system, we use two elicitation techniques, questionnaire and interview technique. The advantage of this system is that our system didn’t need use online and all data will stored in a database and can print as a report. To get the data used in making this system, we used two elicitation techniques namely questionnaire and interview techniques. The advantage of this system is that our system does not need to be used online and all data will be stored in a database and can be printed as a report. Another benefit gained is that all teaching staff, both permanent teachers (PNS) or non-permanent  teachers can  use the system